Is deafness etiology important for prediction of functional outcomes in pediatric cochlear implantation?. (June 2014) - Varga, Lukáš; Kabátová, Zuzana; Mašindová, Ivica; Nechojdomová, Daniela; Gašperíková, Daniela; Klimeš, Iwar; Profant, Milan
Abstract Conclusions: Implanted children with GJB2 mutations tended to achieve better functional outcomes than the two control groups, although clear-cut significance was not always achieved. Hearing loss etiology may be considered as one of the important predictors, but complex influence of other factors on postoperative performance should be included in cautious individual counseling. Objective: This study aimed to detect possible associations between hearing loss etiology and postoperative rehabilitation outcomes in prelingually deaf children, with a particular focus on hereditary deafness caused by connexin mutations. Methods: Eighty-one of 92 prelingually deaf implanted children, tested for DFNB1 mutations, were divided into 3 etiology groups and underwent audiological evaluation in tone audiometry, speech audiometry, monosyllabic words, and categories of auditory performance (CAP), conducted 1, 3, and 5 years after implantation. Results: Statistically significant differences (p < 0.05) for tone audiometry were obtained, particularly after the first and third year post implantation, between 'connexin' and 'known' etiology groups. In speech audiometry, the monosyllabic word test, and CAP, the connexin group of children scored significantly better than the two control groups only after 3 and 5 years. Although the rate of excellent performers was higher in the connexin group, poor results were achieved in all groups in similar proportion.